Analisis Penetapan Harga Pokok Produksi Pada CV Gerai Seni Konveksi Palembang - Winda Apriyani; Eka Jumarni Fithri (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This Final Report aims to assist the company in calculating and compiling reports on the cost of production, considering its significance in the progress of CV Gerai Seni Konveksi. The data used is primary and the object includes the calculation of the cost of production for orders for shirts, sports t-shirts and PDl vests. From the data obtained, problems were found at CV Gerai Seni Konveksi Palembang, namely the lack of proper classification of the elements of the cost of production. Apart from that, the company has not allocated depreciation costs for electricity and equipment, and has not calculated the cost of production carefully. Based on this, the author suggests that companies classify the elements of cost of production accurately, including raw materials, labor costs, depreciation of electricity costs, and depreciation costs of machinery and equipment into a cost calculation that reflects the actual costs.